2022
DOI: 10.18844/wjet.v14i4.6592
|View full text |Cite
|
Sign up to set email alerts
|

Using motivation to improve learning achievement with a chatbot in blended learning

Abstract: Chatbots have the potential to be used as motivational learning tools, particularly for boosting academic performance. The purpose of this study is to construct a Facebook Messenger chatbot to promote accomplishment through the use of blended learning, guided by the ARCS (attention, relevance, confidence, satisfaction) motivation model that compares how engagement works, and explores the chatbot in terms of its usability. Integrated with Facebook Messenger, chatbot software was designed to answer inquiries bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(21 citation statements)
references
References 20 publications
0
1
0
Order By: Relevance
“…Mendez et al [35] shifted their attention to constructing a conceptual framework for an ECA and implied that higher user satisfaction indicates a better quality of the system as well as higher user trust and willingness to use it. Also, Chaiprasurt et al [37] pointed out the importance of motivating students to use the ECA through motives like a grade bonus, while Rooein et al [38] indicated the importance of promoting the application of the agent by motivating and encouraging students to use it since students are not always keen on this technology. Finally, Fryer et al [39] indicated that students have to perceive the agent as a tool that will help them comprehend the learning material better than their usual way of studying in order to utilize it fully.…”
Section: Suggestions For Applying An Eca and Motivating Studentsmentioning
confidence: 99%
See 3 more Smart Citations
“…Mendez et al [35] shifted their attention to constructing a conceptual framework for an ECA and implied that higher user satisfaction indicates a better quality of the system as well as higher user trust and willingness to use it. Also, Chaiprasurt et al [37] pointed out the importance of motivating students to use the ECA through motives like a grade bonus, while Rooein et al [38] indicated the importance of promoting the application of the agent by motivating and encouraging students to use it since students are not always keen on this technology. Finally, Fryer et al [39] indicated that students have to perceive the agent as a tool that will help them comprehend the learning material better than their usual way of studying in order to utilize it fully.…”
Section: Suggestions For Applying An Eca and Motivating Studentsmentioning
confidence: 99%
“…[39] Students should be motivated to utilize the ECA. [37,38] Suggestions and concerns about the teaching process were also presented. Fryer et al [39] implied that teachers should not use the ECA as the main tool of the teaching process, but rather as a supportive tool.…”
Section: Suggestion Referencesmentioning
confidence: 99%
See 2 more Smart Citations
“…Chatbots have progressively been deployed in various fields, such as commerce, the service industries, and education. Moreover, some studies (Perez et al, 2020;Rapp et al, 2021;Smutny & Schreiberova, 2020;Chaiprasurt et al, 2022;Clarizia et al, 2018) show that chatbots are ideal for potentially changing the methods of students' learning and facilitating their access to relevant information according to the educational framework.…”
Section: Introductionmentioning
confidence: 99%